2017
DOI: 10.1371/journal.pone.0170562
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biotreatment of Actual Textile Wastewater in a Continuous Sequential Rice Husk Biofilter and the Microbial Community Involved

Abstract: Textile dying processes often pollute wastewater with recalcitrant azo and anthraquinone dyes. Yet, there is little development of effective and affordable degradation systems for textile wastewater applicable in countries where water technologies remain poor. We determined biodegradation of actual textile wastewater in biofilters containing rice husks by spectrophotometry and liquid chromatography mass spectrometry. The indigenous microflora from the rice husks consistently performed >90% decolorization at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…(Wang et al, 2009), Pseudomonas sp. (Forss et al, 2017), Shewanella sp. (Wang et al, 2015), Aeromonas sp.…”
Section: Bacterial Degradation Of Anthraquinone Dyesmentioning
confidence: 99%
“…(Wang et al, 2009), Pseudomonas sp. (Forss et al, 2017), Shewanella sp. (Wang et al, 2015), Aeromonas sp.…”
Section: Bacterial Degradation Of Anthraquinone Dyesmentioning
confidence: 99%
“…Although the present study has evaluated the degradation process of one dye considering different carriers, previous studies of Forss et al [14] have shown that actual textile wastewater can affect degradation differently. Moreover, an actual wastewater stream might change content depending on different process flows.…”
Section: Discussionmentioning
confidence: 95%
“…It has been applied to remove organic compounds and the colour of textile effluents, due to their low cost, simple operation and maintenance [2,3,9]. Bacteria are performing most of the degradation in the treatment; however, fungi are also found associated in the consortia [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioremediation is the microbial clean up approach, microbes can acclimatize themselves to toxic wastes and new resistant strains develop naturally, which can transform various toxic chemicals to less harmful forms [11]. Microbial processes can substantially contribute to efficient and reliable degradation of actual textile waste water [12]. Use of microorganisms for remediation purpose is thus a possible solution for environmental pollution since it includes sustainable remediation technologies.…”
Section: Introductionmentioning
confidence: 99%